Vipassana Innovation from Beginning to Practicing Technics and Enlightenment Process for Suffering Releasing - Atsadonsak, Nunthanat (International Journal of Psychosocial Rehabilitation, 2020)
this article aims to show Vipassana Innovation of Practicing Technics and Enlightenment Process for Suffering Releasing. Because suffering affects to people’s holistic health both physical and mental, social relation and wisdom creation. If people lack of suffering understanding and confrontation accepting, it will lead to a crisis of holistic health as losing of physical and mental balance, affect to the quality of life, and cause the increasing anxiety and depression, and finally, the suicide crisis. By the method of Vipassana meditation practice in Theravada Buddhism bases on the Pure Vipassana practice, calls “Suddhavipassanāyānika”, that exposes how to understand and loose from suffering by using momentary concentration (Khaṇika-samādhi), a high frequency continually awareness in perceiving the Common Characteristics (Sāmañña-lakkhaṇa) of physical and mental components such as Five Aggregates (Pañca-khandha), in accordance with the Four Foundations of Mindfulness (Satipaṭṭhāna). This process leads to the enlightenment by suffering liberation, entered the Knowledge of Path (Maggañāna) to be The Perfect One (Arahanta), and finally the discrimination of highest wisdom in Buddhism (Paṭisambhidā). Even the result of practicing has not reached the enlightenment, but those can affect some changes of suffering recognition. Results from benefits of the Four Mindfulness practices through many empirical researches which integrated with Cognitive Behavioral Therapy (CBT) for physical and mental development. Therefore, the researchers design Vipassana Innovation to an application, develop a prototype product for presenting a media to demonstration of meditation practice, lead to the practice Vipassana correctly. In addition, it provides guidance to adjust the suffering recognition and confrontation in daily life from video conference system, which supports to converse with experts around the world, and having experience from Vipassana Institute. This prototype application offers the creative way to bring oneself loose from suffering online, create sustainable development for the global society by a happy living without limits.